Comparative analysis of the efficiency and dentoskeletal effects between distalization of molars with Hilgers pendulum and miniscrew-anchored cantilever for Class II correction - Campos, Cassio Bernard Alves (2024)
This study aimed to compare the efficiency and dentoskeletal changes in the treatment of Class II malocclusion using the miniscrew-anchored cantilever and the pendulum appliance. To evaluate dentoskeletal changes before and after distalization, cephalometric analysis and superimposition of digital models were used. In this analysis, the sample consisted of 52 patients divided into two groups, according to the treatment received. The miniscrew group (MG) consisted of 23 patients treated with upper molar distalization using the miniscrew-anchored cantilever. The pendulum group (PG) consisted of 29 patients treated with distalization of upper molars with the pendulum appliance. To evaluate the efficiency of the treatment, model analysis was performed before and after orthodontic treatment using the Peer Assessment Rating (PAR) and American Board of Orthodontics Objective Grading System (OGS) indexes. In this evaluation, 28 patients were divided into 14 patients in MG and 14 patients in GP. Intergroup comparisons were performed using the T and Mann-Whitney tests. The MANCOVA test was used to evaluate the influence of covariates (P<0.05). The results showed that both devices effectively achieved molar distalization, with the MG showing greater control of side effects, such as loss of anchorage, during distalization compared to the PG. The PG showed a greater increase in overjet. Furthermore, the MG presented significantly shorter treatment time and better occlusal results than the PG, with lower final PAR, higher percentage of PAR reduction, higher Treatment Efficiency Index (TEI) and lower alignment/rotation and occlusal relationship scores in the OGS index. The miniscrew-anchored cantilever proved to be more efficient in correcting Class II malocclusion compared to the pendulum device. These findings highlight the importance of skeletal anchorage in molar distalization, as it improves occlusal results and reduces treatment time.